Childhood predictors of lifetime suicide attempts and non-suicidal self-injury in depressed adults. (February 2016) - Johnstone, Jeanette M; Carter, Janet D; Luty, Suzanne E; Mulder, Roger T; Frampton, Christopher M; Joyce, Peter R
Objective: Adverse childhood experiences are well-recognized risk factors for a variety of mental health issues, including depression, suicide attempts and non-suicidal self-injury. However, less is known about whether childhood adversity, in the form of low parental care, overprotection and abuse, is associated with suicide attempt and non-suicidal self-injury within a sample of depressed adults. Method: The sample of outpatients ( n = 372) was drawn from two randomized depression trials. Childhood adversity variables, depression severity, age of first depressive episode (major depression episode onset), lifetime suicide attempt and non-suicidal self-injury were recorded at baseline. The association between variables and outcome measures was examined using partial correlations, univariate and multivariate logistic regressions. Results: Low maternal care was significantly associated with suicide attempt; low paternal care was associated with non-suicidal self-injury; overprotection was not associated with either outcome. Other risk factors for suicide attempt were major depression episode onset and baseline depression severity. Major depression episode onset was also a risk factor for non-suicidal self-injury. Abuse, regardless of how it was measured, was not significantly associated with either behaviour after adjusting for its correlations with low maternal or paternal care. Conclusion: In this sample of depressed adults, the quality of ongoing, intra-familial relationships, as measured by levels of parental care, had a greater impact on suicide attempt and non-suicidal self-injury than abuse. As the findings were not a priori hypotheses, they require replication. Although the cross-sectional study design limits causal determination, the findings suggest different childhood risk factors for suicide attempt and non-suicidal self-injury and underscore the impact of low parental care on these two behaviours. These findings signal to clinicians the importance of asking specifically about suicide attempts, and non-suicidal self-injury, as well as levels of parental care in childhood. When endorsed, low parental care may be considered an important factor in contextualizing a patient's depression and potential risk for suicide and non-suicidal self-injury.